Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fonc.2022.1025805
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils in pancreatic cancer: Potential therapeutic targets

Abstract: Pancreatic cancer is a digestive system malignancy and poses a high mortality worldwide. Traditionally, neutrophils have been thought to play a role in acute inflammation. In contrast, their importance during tumor diseases has been less well studied. Generally, neutrophils are recruited into the tumor microenvironment and exert inflammation and tumor-promoting effects. As an essential part of the tumor microenvironment, neutrophils play diverse roles in pancreatic cancer, such as angiogenesis, progression, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 136 publications
(151 reference statements)
0
7
0
Order By: Relevance
“…Besides, there have been reports indicating that Tregs inhibits the cytotoxicity of CD8 + T cells, resulting in a negative outcome for HCC ( Moghaddam et al, 2022 ; Zheng et al, 2017 ). An increasing number of studies have shown that neutrophil not only play a crucial role in creating an immunosuppressive environment that supports tumor development, but also act as a driving force in tumor progression ( Jiang et al, 2022 ; Shaul & Fridlender, 2019 ). It also plays an important driving role in HCC ( Geh et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, there have been reports indicating that Tregs inhibits the cytotoxicity of CD8 + T cells, resulting in a negative outcome for HCC ( Moghaddam et al, 2022 ; Zheng et al, 2017 ). An increasing number of studies have shown that neutrophil not only play a crucial role in creating an immunosuppressive environment that supports tumor development, but also act as a driving force in tumor progression ( Jiang et al, 2022 ; Shaul & Fridlender, 2019 ). It also plays an important driving role in HCC ( Geh et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The longitudinal age curve, on the contrary, denotes the cohort-and period-adjusted longitudinal age-speci c rates. Finally, period (cohort) RRs are period (or cohort) relative risk adjusted for age and nonlinear cohort (or period) effect in a period (or cohort) versus the reference period (or cohort) [12]. In the age-period-cohort analysis, the number of deaths and the population were arranged into consecutive 5-year periods from 1990 to 2019 and successive 5-year age groups from 25 to 29 and from 90 to 94.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Neutrophils respond to low-dose IFN-β and transform into anti-tumor subsets that secrete CCL3, CXCL9, and other chemokines, promoting immunity by recruiting CD8 + T cells. They also increase TNF-α and ROS expression to amplify cytotoxicity ( 61 ). Furthermore, antineoplastic neutrophils mediate the release of IL-1 and hepatocyte growth factor (HGF) to exert antibacterial activity and increase the production of iNOS to kill tumor cells, respectively ( 61 ).…”
Section: Major Cellular Components In the Tme Of Pdacmentioning
confidence: 99%
“…They also increase TNF-α and ROS expression to amplify cytotoxicity ( 61 ). Furthermore, antineoplastic neutrophils mediate the release of IL-1 and hepatocyte growth factor (HGF) to exert antibacterial activity and increase the production of iNOS to kill tumor cells, respectively ( 61 ). TGF-β induced TANs differentiation of tumor subpopulations ( 62 ).…”
Section: Major Cellular Components In the Tme Of Pdacmentioning
confidence: 99%
See 1 more Smart Citation